Como comen los dinosaurios? - Yolen, Jane; Teague, Mark; Alvarez-Salas, Pepe. (New York : Scholastic, 2005)
Describes how a dinosaur eats, with no rude noises and while sitting very still.
"Scholastic en espanol"--Cover.
Keywords: Table etiquette -- Juvenile fiction; Etiquette -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Etiqueta en la mesa -- Novela juvenil; Etiqueta -- Novela juvenil; Dinosaurios -- Novela juvenil